Effect of Litsea lancifolia leaf extract on glucose transporter 4 translocation and glucose uptake in 3T3L1 cell line - Murad Alsawalha; Abeer Mohammed Al-Subaie; Reem Yousuf Al-Jindan; Srinivasa Rao Bolla; Janardhana Papayya Balakrishna; Padma Kanchi Ravi; Shiva Shankar Reddy Gollapalli; Vishnu Priya Veeraraghavan; Aruthra Arumugam Pillai; Joel Palpath Joseph; Surapaneni Krishna Mohan (Wolters Kluwer Medknow Publications, 2019)
Background: Numerous synthetic drugs have been recommended as a remedy for diabetes, but their role in hypoglycemic effects are diverse. The side effects associated with these drugs due to their extended use led scientists to find unconventional medicines with no or little side effects. Aim: This study was aimed at assessment of in vitro antidiabetic activities of methanolic extract of Litsea lancifolia leaves by using 3T3L1 cell line. Materials and Methods: The cytotoxic effect of the leaf extract was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The glucose uptake-inducing capabilities and its correlation with glucose transporter 4 (GLUT4) translocation were measured by flow cytometry in 3T3L1 cells. In addition, the inhibitory effect of L. lancifolia leaf extract on α-amylase activity and α-glucosidase activity was determined by colorimetric methods. Results: Different concentrations of L. lancifolia leaf extract did not show any toxicity on 3T3L1 cells, after the treatment for 24h. On stimulation with leaf extract, 60.22% and 86.26% of 3T3L1 cells showed glucose uptake and GLUT4 expression, respectively. The colorimetric assays showed that the methanolic leaf extract of L. lancifolia has a significant inhibitory effect on the activity of α-amylase enzyme and α-glucosidase enzyme with inhibitory concentration (IC50) value of 248.65 µg/mL and 229.61 µg/mL, respectively. Conclusion: On the basis of the results of this study, it is evident that L. lancifolia leaf extract showed promising anti-diabetic effect when compared to the standard drugs metformin and acarbose and was nontoxic to 3T3L1 cells. Thus, it can be further investigated to recommend as a possible alternative treatment in antidiabetic applications.